Visual Attention and Poor Sleep Quality - Abdolalizadeh, Amirhussein; Nabavi, Samaneh (Frontiers in Neuroscience, 2022)
Background: Sleep deprivation disrupts visual attention, however, the effects of chronic poor sleep quality on it are not understood. Dorsal (DAN) and ventral (VAN) attention networks are involved in visual attention and search (VSA), with DAN being important for serial and VAN for parallel “pop-out” visual search. Objective: Evaluate correlates of sleep quality with visual attention and search, functional, and tracts’ properties of DAN and VAN Method: We recruited 79 young male subjects and assessed sleep quality with Pittsburgh Sleep Quality Index (PSQI), dividing subjects into poor (PS) and good sleepers (GS) based on a cut-off of 5. Daytime sleepiness, sleep hygiene, depression, and anxiety levels were also evaluated. We assessed VSA using a computerized match-to-sample (MTS) task. We extracted functional networks and tracts of VAN and DAN and statistically assessed group differences in task performance and imaging covarying for age, depression, and anxiety. An interaction model with MTS × group was also done on imaging. Results: 43.67% of subjects were PS. Sleep quality significantly correlated with daytime sleepiness, sleep hygiene, depression, and anxiety (all p < 0.001). No between-group differences were seen in task performance, and functional or tract properties of the attention networks. Interaction analysis showed task performance being highly reliant on DAN in PS and on VAN in GS. Conclusion: Our findings show no association between sleep quality and VSA in task performance and imaging correlates of attention network. However, unlike the GS group, poor sleep quality is associated with VSA being more reliant on DAN and less on VAN.